Intraarticular administration of chondroitin sulfate in experimental osteoarthritis - Nosivets, Dmitriy (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Osteoarthritis (OA) is generally a progressive disease that affects synovial joints, resulting in abnormalities to articular cartilage subchondral bone, synovium, and adjacent soft tissues. The purpose of this work was to investigate the specific activity of chondroitin sulfate (CS) in intra-articular and intramuscular administration to laboratory rabbits in experimental OA. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. OA was induced in rabbits by a single injection of mono-iodoacetate in knee joint. CS was administered intra-articularly and intramuscularly. The analysis of biochemical markers and macroscopic assessment of rabbit knee joints was performed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Intramuscular and intra-articular injection of CS reduces the intensity of the degenerative-dystrophic process due to the impact on inflammatory and the activation of anabolic mechanisms. Intra-articular administration of CS leads to a greater increase in the level of factors of bone and cartilage formation and a greater decrease in the levels of factors of the acute phase of inflammation and factors that destroy the cartilage matrix. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Intramuscular administration of CS revealed a lower intensity of destructive changes in the cartilaginous surface of the knee joint, and intramuscular – the absence of cartilage destruction and defects of the cartilaginous surface, which indicates the peculiarity of the topical effect of the CS.